Descriptive Cross-Sectional Study on Knowledge and Practices on Birth Preparedness and Complication Readiness among Primigravida Women Attending Uasin Gishu Sub County Hospitals. - Odongo, Philip; Ambale, Erick; Ryan, Milton; Jemurgor, Marion; Kipngetich, Edwin; Getanda, Amos; Milimo, Benson (Student's Journal of Health Research Africa, 2025)
Background: Birth preparedness refers to the actions taken by pregnant women and their families to ensure a safe childbirth and prepare for potential emergencies. The goal is to reduce global maternal mortality to less than 70 per 100,000 live births. In Kenya, the maternal mortality ratio is 362 per 100,000. Many pregnant women, including primigravidae, lack knowledge about birth preparedness and complication readiness (BP/CR). Objectives: This study aimed to determine knowledge and practices regarding BP/CR among primigravida women attending Uasin Gishu sub-county hospitals. Specific objectives included assessing knowledge and practices of BP/CR and identifying factors associated with BP/CR among primigravidae. Methods: A descriptive cross-sectional study using quantitative methods was conducted. The target population consisted of primigravida women aged 15-49 years who attended antenatal clinics in Uasin Gishu. A sample of 264 women was selected using systematic sampling. Data were analyzed using descriptive statistics and Chi-square tests to assess associations between variables at a 95% confidence interval. Results: Notably, 72.7% had not received BP/CR information from midwives. However, 70.8% knew labor could start before the due date, and 66.3% were aware of the potential need for blood transfusion. Preparations included saving for transport (73.5%), identifying delivery locations (76.1%), and birth companions (71.6%). Factors such as age, level of education, income, and trimester values were statistically significant, showing an effect on the BPCR. Conclusion: Gaps in preconception clinic attendance and BP/CR information from midwives were noted. Nevertheless, awareness of EDD and preparation for emergencies were high. Statistical analyses highlighted the need for targeted education for younger primigravidae. Recommendations: Enhance BP/CR education during antenatal visits, promote preconception clinics, increase antenatal visit attendance, facilitate access to blood donors, and ensure financial and transportation support for low-income women